Supply chain cost analysis for additively manufactured biomedical implants. Issue 3 (2nd July 2020) - Chowdhury, Sudipta; Francis, Jack; Marufuzzaman, Mohammad; Bian, Linkan
ABSTRACT: Biomedical implants fabricated through Additive Manufacturing (AM) yield opportunities to speedily respond to customer demand in producing patient-specific customised parts while simultaneously reducing the inventory level and delivery costs. No research efforts, to the best of authors knowledge have been dedicated to a holistic quantitative analysis of the costs of supply chain integrated with AM facilities, e.g. inventory cost, transportation cost, product lead time, post-processing cost, and so forth. In this study, we propose a stochastic model to quantify the supply-chain level costs associated with the production of biomedical implants using AM techniques. Sample Average Algorithm (SAA) is employed to solve the model within a reasonable time frame. The optimisation model determines the number of AM facilities to be established and the volume of product flow between different tiers of the supply chain network (e.g. from manufacturing facilities to post-processing facilities and finally to customers/hospitals). A real-world case study has been developed that focuses on the use of biomedical implants for customers in the state of Mississippi (MS). A series of experimental studies are developed to understand how the supply chain structure varies as the demand and demand variability for biomedical implants changes.